Competitiveness of Public Services, Non-Formal Education Institutions Center of Education Indonesia - Ishak, Muhammad; Niswaty, Risma; Guntur, Muhammad (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This research aims to reveal (1) the form of competitiveness of the public services provided by non-formal education Study Center of Indonesia, (2) public perceptions of the competitiveness of the public services provided by the Study Center of Indonesia, (3) as well as the factors that is affecting the competitiveness of the public services of the Study Center of Indonesia. This research is carried out using a qualitative research and qualitative descriptive approach. Data collection techniques used in this study are observation, interviews and documentation. The data obtained were analyzed using qualitative descriptive with the stages of reducing data, displaying data and taking conclusions. The data validation technique is triangulation technique. The results of this study indicate that (1) the form of competitiveness of public services provided by the Study Centers of Indonesia educational institutions are a) services and learning programs that include learning programs (preparation for and entry into a university), academic mentoring programs, service oriented needs of students, a collaboration program b) alumni marketing strategy. (2) public perceptions of the competitiveness of public services provided by the non-formal Study Center of Indonesia, namely a) services as needed, and b) economical (3) factors that influence the competitiveness of the non-formal educational institutions Study Center of Indonesia, namely a ) human resource competencies owned, b) institutional regulations, and c) supporting facilities.